Implementasi Pembelajaran Membaca Permulaan Melalui Media Flash Card Pada Anak Kelompok B di TK Al-Islam 10 Surakarta Tahun Ajaran 2015/2016 - Handayani, Mulat; , Drs. Ilham Sunaryo, M.Pd AUD (2016)
The purpose of this study was to describe the beginning of the implementation of learning to read through a flash media card and to determine the constraints faced by the teacher at the time of learning to read the beginning of the flash media card. This study is a qualitative descriptive approach. This research was conducted in TK Al-Islam 10 Surakarta, where children in group B are subject in the academic year 2015/2016. This research is a collaboration between classroom teachers, researchers, and school principals. Data collection techniques in this study using observation, interviews and documentation as compliance data. Analysis of the data in this study using the analysis model of Miles and Huberman, is to perform data reduction (data reduction), presentation of data (data display), and conclusion drawing. Results of research on learning implementation Early reading through a flash media card is a flash media card can be used for learning to read at the beginning of kindergarten students at the Al-Islam 10 Surakarta and has an important role in reading readiness at the next level. Keywords: Early reading, flash media card